STRUKTUR TUBULUS SEMINIFERUS MENCIT (Mus musculusL.) SETELAH PAPARAN EKSTRAK ETANOL DAUN MIMBA (Azadirachta Indica A.Juss) - Sarifudin Avycena; Agung Janika Sitasiwi; Siti Muflcihatun Mardiati (Jurnal Pro-Life, 2020)
Neem leaves are one of the traditional medicinal plants (Azadirachta indica A Juss). Neem leaves contain an activecomposition as an antifertility such as azadirachtin, flavonoids, saponins, nembeen and nimbidin. SpermatogenicIndex of male mice (Mus musculus L) after being given ethanol extract from the leaves of the mimba (Azadirachtaindica A. Juss). This study used a completely randomized design (CRD) with 2 control groups (aquades) andtreatment (giving the leaves of the mangosteen ethanol extract at a dose of 14 mg / KgBB / day) with 15 replications.The treatment was given orally with a volume of 0.2 ml for 21 days. The 22 days of the testes were isolated, weighedand made histological preparations using a paraffin method with a thickness of 5 μm, and staining of HematoxylinEosin (HE). Observation of seminiferous tubule structure and measurement of seminiferous tubule diameter wascarried out in 4 fields of view. The Spermatogenic Index values (SI) was determined by the number of phases ofeach field specified in the seminiferous tubules. Data were analyzed by t test with a confidence level of 95%. Theresults of the analysis showed not significant different on body weight, testicular weight and diameter of theseminiferous tubules. Spermatogenic Index observations showed that the control group had a dominant fase of 5while the treatment group had dominant fase of 4.The research concluded that the administration of mimba leavesethanol extract was recommended as an antifertility of male animals. Keywords: Neem; seminiferous Tubules; Spermatogenic Index